Detection and identification of Xanthomonas pathotypes associated with citrus diseases using comparative genomics and multiplex PCR - Fonseca, Natasha P.; Felestrino, Érica B.; Caneschi, Washington L.; Sanchez, Angélica B.; Cordeiro, Isabella F.; Lemes, Camila G.C.; Assis, Renata A.B.; Carvalho, Flávia M.S. [UNESP]; Ferro, Jesus A. [UNESP]; Varani, Alessandro M. [UNESP]; Belasque, José; Setubal, Joao C.; et al. (PeerJ, 2019)
Background. In Citrus cultures, three species of Xanthomonas are known to cause distinct diseases. X. citri subsp. citri patothype A, X. fuscans subsp. aurantifolii pathotypes B and C, and X. alfalfae subsp. citrumelonis, are the causative agents of cancrosis A, B, C, and citrus bacterial spots, respectively. Although these species exhibit different levels of virulence and aggressiveness, only limited alternatives are currently available for proper and early detection of these diseases in the fields. The present study aimed to develop a new molecular diagnostic method based on genomic sequences derived from the four species of Xanthomonas. Results. Using comparative genomics approaches, primers were synthesized for the identification of the four causative agents of citrus diseases. These primers were validated for their specificity to their target DNA by both conventional and multiplex PCR. Upon evaluation, their sensitivity was found to be 0.02 ng/µl in vitro and 1.5 × 104 CFU ml−1 in infected leaves. Additionally, none of the primers were able to generate amplicons in 19 other genomes of Xanthomonas not associated with Citrus and one species of Xylella, the causal agent of citrus variegated chlorosis (CVC). This denotes strong specificity of the primers for the different species of Xanthomonas investigated in this study. Conclusions. We demonstrated that these markers can be used as potential candidates for performing in vivo molecular diagnosis exclusively for citrus-associated Xanthomonas. The bioinformatics pipeline developed in this study to design specific genomic regions is capable of generating specific primers. It is freely available and can be utilized for any other model organism.
Keywords: Citrus canker; Comparative genomics analysis; Molecular diagnostic; Multiplex PCR; Xanthomonas